Theoretical and practical aspects of professional image formation in the process of development of professional speaking competence of college students - Soroka, Olga; Kalaur, Svitlana (Social work and education, 2023)
The article updates the problem of professional image formation in the process of developing the professional speech competence of college students. It is emphasized that the study of the student’s image is especially relevant today. It is up-to-date as the requirements for the future professional, as for a modern competitive specialist, are constantly growing. There are analyzed modern scientific approaches to the interpretation of the concepts of “image” and "professional image". It was found that the professional image is the image that must be created purposefully and consciously in order to achieve professional and personal goals, professional growth and self-development.There are defined structural components of the specialist’s image: external, procedural and internal. The external component includes facial expressions, gestures, timbre and strength of voice, clothes, manners, gait. Appearance can create a positive mood at work. Or on the contrary, it can hinder understanding, facilitating or hindering communication and interaction between people. The procedural component of the image is specified by such forms of communication as professionalism, plasticity, expressiveness, etc. The internal component is focused on the inner world of a person, ideas about his spiritual and intellectual development, values, interests, personality in general.It was concluded that a characteristic feature of image training is its communicative orientation. That is why the article proposes to use educational methods focused on contact and interaction. It ensures the construction of a dialogue, in the formation of the professional image of junior professional bachelors.It is suggested using training and dialogue, among the most effective forms of interactive training of college students. The article presents the training “Professional image” aimed at forming a certain image in the process of developing the professional speech competence of college students. It includes verbal and non-verbal parts. The developed training is designed for eight lessons, which do not exclude invariance. They can be replaced, shortened and included in the structure of any lesson from various educational disciplines, in particular “Psychology” or “Ukrainian language (for professional direction”.